MASKULINITAS DALAM TRADIS ADU KAKI: TINJAUAN SOSIOLOGI KEKERASAN FISIK DAN KEKERASAN VERBAL - Widyantari, Ni Luh; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This study analyzes the Tamblang Waluh tradition as a cultural practice that represents the mechanism of the formation and strengthening of masculinity through physical and verbal violence. The tradition that takes place in the Bungaya Traditional Village not only functions as a cultural expression, but also becomes a space for the reproduction of masculine dominance values ??in the social structure of the local community. Pierre Bourdieu's Masculine Dominance Theory is the basis for thinking in this study which seeks to examine how violence in this tradition is constructed, maintained, and inherited as part of the identity of youth masculinity. The research method used is descriptive qualitative through in-depth interviews, participatory observation, and documentation to explain the practice of violence in it. The results of this study reveal that the Tamblang Waluh tradition is a social arena that reproduces masculinity through the mechanism of legitimizing physical violence and verbal violence. Through physical violence, it can be seen from the foot fights carried out by participants called metinjakan as a medium for testing the strength and courage of young people. Meanwhile, verbal violence comes from the shouting of the word katuk/teli katuk by young people who are participants in the Metinjakan, indirectly confirming the position of male dominance. The finding of masculine dominance in this tradition operates through the concept of social construction of the body, women in the symbolic wealth economy, and symbolic violence becomes a structure that supports the legitimacy of violence as part of the masculinity of the youth of Bungaya Traditional Village. So that violence in the Tamblang Waluh tradition is not only a cultural expression but also becomes one of the mechanisms for young people in producing and maintaining masculine identity.   Keyword: masculinity, tradition, physical violence, verbal violen ce